2020
DOI: 10.1111/ene.14511
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis and bridging therapy in patients with acute ischaemic stroke and Covid‐19

Abstract: Background and purpose Comorbidity of acute ischaemic stroke with Covid‐19 is a challenging condition, potentially influencing the decision of whether to administer intravenous thrombolysis (IVT). We aimed to assess the 1‐month outcome in ischaemic stroke patients with Covid‐19 infection who received IVT alone or before thrombectomy (bridging therapy). Methods As a collaboration initiative promoted by the Italian Stroke Organization, all Italian stroke units (n = 190) were contacted and invited to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…For cerebrovascular disease, some of the predictors of poor outcome were in line with the experience in non-COVID stroke cases, such as older age, higher NIHSS at admission, baseline glucose, and creatinine levels, while others appear to be more specific to this particular population (e.g. thrombocytopenia, lymphocytopenia, and elevated levels of D-dimer and LDH) [ 7 , 11 , 13 , 19 , 60 , 62 ].…”
Section: Outcomementioning
confidence: 82%
See 1 more Smart Citation
“…For cerebrovascular disease, some of the predictors of poor outcome were in line with the experience in non-COVID stroke cases, such as older age, higher NIHSS at admission, baseline glucose, and creatinine levels, while others appear to be more specific to this particular population (e.g. thrombocytopenia, lymphocytopenia, and elevated levels of D-dimer and LDH) [ 7 , 11 , 13 , 19 , 60 , 62 ].…”
Section: Outcomementioning
confidence: 82%
“…Importantly, the outcome of COVID-19-related stroke cases was significantly worse than that of non-COVID stroke cases in 2 different studies performed in Italy and USA, respectively [ 59 , 60 ]. The mortality rate was particularly high in cases with stroke ensuing in association with severe respiratory disease requiring ICU admission [ 7 ].…”
Section: Outcomementioning
confidence: 99%
“…This is true for both patients who received intravenous thrombolysis alone and those who received it as a bridging therapy before undergoing thrombectomy. 18 Additionally, a study has shown that having a poor outcome after receiving reperfusion therapies was independently associated with SARS-CoV-2 infection. 19 This finding is in agreement with another study done by Escalard et al, describing that poor outcome could be related to the prothrombotic state due to SARS-CoV-2 infection causing re-occlusions after receiving reperfusion therapies.…”
Section: Discussionmentioning
confidence: 99%
“…There may be reluctance in using acute revascularization treatments due to presence of elevated concentration of inflammation and hypercoagulability markers 4,6,7 and reports of high mortality in patients with SARS-CoV-2 infection who were treated with acute revascularization treatments. [1][2][3] Patients with SARS-CoV-2 infection may be excluded due to hepatic dysfunction 5 and coagulopathy (elevated prothrombin time, international normalized ratio, activated partial thromboplastin time, or reduced platelet count). The relatively high rate of renal insufficiency with subsequent acute kidney injury in patients with SARS-CoV-2 infection 26 may delay or preclude administration of contrast for computed tomography angiography and/or perfusion to identify appropriate candidates.…”
Section: Utilization Of Acute Revascularization Treatmentsmentioning
confidence: 99%
“…Our understanding of outcomes in acute ischemic stroke patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection following acute revascularization treatments (as intravenous thrombolysis and/or thrombectomy) is based on small case series. [1][2][3] . An international panel 4 cautioned regarding the potential for high rate of death or disability and post thrombolytic intracerebral hemorrhage (ICH)s in acute ischemic stroke patients with SARS-CoV-2 infection due to elevated concentrations of inflammation and hypercoagulability markers such as leukocytosis, and C reactive protein and D dimers and multisystem dysfunction.…”
Section: Introductionmentioning
confidence: 99%